The Effect Of Health Education On Blood Pressure Behavior Behavior In Hypertension Patients - Hamdana; A.Nurlaela Amin; Misra (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2018)
Based on the amount of data obtained from Bonto Bangun health center wherein 2015 there were only 305 people suffering from hypertension, in 2016 there were 236 people, and in 2017 there was an increase in hypertension, namely 356 people and in 2018 for 3 months there were 70 people suffering from hypertension. The purpose of this study is to know the effect of health education on blood pressure reduction behavior in hypertensive patients in the work area of ​​Puskesmas Bonto Bangun Kec, Rilau Ale, Bulukumba District. This type of research is a pre-experimental study with a pre-experimental approach: one group pretest-posttest design. Simple random sampling data collection techniques with the number of samples in this study as many as 36 respondents through questionnaire sheets. Data analysis using paired t-test with significance level α = 0.05. The results of data analysis showed that the behavioral variable p = 0,000, it can be concluded that there is an effect of health education on blood pressure reduction behavior in hypertensive patients in the work area of ​​Puskesmas Bonto wake. Conclusion there is the influence of health education on blood pressure reduction behavior in hypertensive patients. Suggestions are expected to be given health education through regular counseling or other media by relevant agencies especially regarding hypertension